Phytochemical Composition, in vitro Studies on α-Amylase and α-Glucosidase Inhibitory Activity of Selected Mangrove Plants (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The purpose of this study is to show the phytochemical composition and in vitro antidiabetic potential in the leaves of Ceriops tagal, Bruguiera cylindrica, and Salvadora persica mangrove plants. The phytochemical composition was studied by qualitative analysis. To determine in vitro antidiabetic activity leaves were subjected to solvent extraction by the Soxhlet method using methanol, ethanol, ethyl acetate, and pet ether and α-amylase, α-glucosidase inhibition assays were performed. The findings indicates that alkaloid, steroid, flavonoid, terpenoid, glycosides, tannin, saponin, phenol, quinones and coumarin principles are present in the leaves of selected mangrove species. Among the selected mangrove species C. tagal leaves recorded the highest antidiabetic activity for both the assay followed by B. cylidrica and S. persica. Overall C. tagal was found highly potent in the antidiabetic activity.